SOSIALISASI WATER AWARENESS KEPADA ANAK-ANAK DI RA TAUFIQURRAHMAN BEJI TIMUR DEPOK - Nuringsih, Kartika; Edalmen (Jurnal Serina Abdimas, 2023)
Depok City as one of the supporting cities for the Special Capital Region of Jakarta faces problems related to waste and water resource management. Regulations have been regulated through regional regulations, but in practice, unconscious behaviour towards environmental hygiene is still found. To support sustainable development, it must be based on public awareness, so it is necessary to socialize the use of clean water to foster water awareness among children. An activity was carried out with RA Taufiqurrahman in Beji Timur Depok to introduce ways to protect and utilize clean water. Starting on November 30, it will be continued on December 6, 2022, involving 35 children, three accompanying teachers and the school principal. This topic is in line with the commemoration of World Handwashing with Soap Day proclaimed by the World Health Organization every October 15th. There are five aspects that are socialized to children including: the benefits of clean water, the characteristics of clean water, sources of clean water, types of water pollution and how to maintain clean water. Followed by the practice of washing hands with soap and ending with hand washing greetings. The evaluation results show that there is an understanding of water awareness so that the support of teachers and parents can help children carry out this habit. Sustainability and stakeholder support can shape the character of Indonesian children who care about the environment so that later they will contribute to supporting the sustainable development of Depok City.